Peri-implantation Sexual Abstinence and Early Placental Positioning: A Randomized Controlled Trial of Placental Location and Pregnancy Outcomes - Ibrahim, Abubakar; Khoo, Martina Irwan; Engku Ismail, Engku Husna; Nik Ahmad Zuky, Nik Syamim Firdaus; Nik Hussain, Nik Hazlina; Mat Zin, Anani Aila; Noordin, Liza; Abdullah, Sarimah; Mahdy, Zaleha Abdullah; Zuky Nik Lah, Nik Ahmad; et al. (Journal of Neonatal Surgery, 2025)
Introduction: The peri-implantation period is critical for blastocyst implantation and placental development. Sexual intercourse during this phase may disrupt implantation, increasing the risk of low-lying placenta and adverse pregnancy outcomes. Evidence on whether peri-implantation sexual abstinence can influence placental positioning and maternal–fetal health is lacking. Methods: We conducted a single-centre randomized controlled trial (Hospital Universiti Sains Malaysia, January 2021–October 2023). Couples were randomized 1:1 to either peri-implantation sexual abstinence (refraining from intercourse for 14 days post-ovulation) or non-abstinence. Pelvic ultrasound at 5–6 and 11–12 weeks assessed implantation, and serial ultrasounds at 18–22, 28–32, and 36–38 weeks monitored placental location and fetal growth. Maternal and neonatal outcomes, including preeclampsia, fetal growth restriction (FGR), preterm birth, NICU admission, and congenital anomalies, were recorded. Results: Of 94 couples screened, 61 were randomized; 33 achieved confirmed pregnancies and entered primary analysis (abstinence n=9; non-abstinence n=24). Low-lying placenta occurred in 0/9 (0.0%; 95% CI 0–33.6%) in the abstinence group and 5/24 (20.8%; 95% CI 7.1–42.2%) in the non-abstinence group (absolute risk difference –20.8 percentage points; Fisher’s exact test p=0.29). No preeclampsia or placenta previa were observed. Secondary outcomes showed no significant differences, though event counts were small. Discussion : Peri-implantation sexual abstinence was associated with a lower point estimate of early low-lying placenta, though not statistically significant in this pilot trial. Findings suggest a potential biological signal warranting larger trials with objective adherence measures to test causality and refine strategies for reducing abnormal placentation. Trial Registration (JEPeM Code for ethical clearance): USM/JEPeM/21030234 This study was registered on 7th July 2021 and conducted in accordance with the Declaration of Helsinki, ICH-GCP Guidelines, CIOMS Ethical Guidelines, and WHO Standards for Health Research Ethics Review.